Radar Attenuation in Enceladus' Ice Shell: Obstacles and Opportunities for Constraining Shell Thickness, Chemistry, and Thermal Structure. Issue 2 (17th February 2023) - Souček, Ondřej; Běhounková, Marie; Schroeder, Dustin M.; Wolfenbarger, Natalie S.; Kalousová, Klára; Steinbrügge, Gregor; Soderlund, Krista M.
Abstract: Enceladus is a dynamic icy moon of Saturn and a leading target for future planetary missions focused on the search for life beyond Earth. For such missions, instruments that can provide geophysical and geochemical context for ice shell and ocean processes are critical to evaluate whether conditions are suitable for life and biosignature detection. Radar sounding is a powerful geophysical technique to probe the thermophysical and chemical properties of icy moons, like Enceladus, and to investigate the subsurface context for the exchange of material and energy between their subsurface oceans, ice shells, and plumes. To inform the scientific potential and instrument performance demands of such a radar‐sounding investigation of Enceladus' ice shell, we adapt and extend previous radar attenuation analysis done for Europa to the configuration and conditions of Enceladus. We also discuss how attenuation (both as an obstacle for the detection of ice shell reflectors and as a signal itself) can help constrain the thermal, physical, and chemical configuration of Enceladus' ice shell and reveal the processes governing the moon's ocean/shell/plume system. Plain Language Summary: Enceladus, a tiny icy moon of Saturn, has been attracting attention since the discovery of its spectacular water jet activity. The jets, sampling the moon's hidden deep ocean, have revealed conditions favorable for the existence of life below the cold outer ice shell. Understanding the long‐term persistence of the ocean, the jets, and their connection to the ice shell and ocean requires reliable knowledge of the shell's physical, thermal, and chemical properties. Ice penetrating radar is a powerful tool for studying ice shells in the planned missions to Jupiter's icy moons. In this paper, we expand and adapt the radar‐based approach to Enceladus in light of the established constraints on the shell's structure and chemistry. We find that although the shell's chemical composition makes direct radar detection of the ice‐ocean interface challenging, the shell's thermal structure enables constraining the thickness—and potentially chemistry—by future missions using echoes from water within the shell. Key Points: We explore radar attenuation within Enceladus' ice shell as a function of its chemistry using a 3D model of its shape and thermal structure Direct radar detection of the ice‐ocean interface is improbable for chloride‐rich shells except for the thin south‐polar region The NH3 eutectic isotherm is a comparatively easy‐to‐detect interface, with the potential to constrain the shell thickness and composition